Influence of the storage on physiological and health quality of pearl millet seeds - Bahry, Carlos André (2008)
This work was carried out with the objective to evaluate physiological and health quality of pearl millet seeds tested just after harvest and after 18 months, in not controlled conditions and cold and dry conditions of storage. Two lots of different origins were evaluated, which were submitted to tests of germination, vigor and health. Comparison between lots and storage conditions was carried out by the test of Tukey at 5% of probability in a completely randomized delineament. Seeds submitted to storage in not controlled conditions presented higher deterioration, evidenced by lower germination and by lower vigor. In cold and dry storage conditions, was observed that seeds initial physiological quality was maintened. Analysis of health quality, showed that the two storage environments were beneficial for the reduction of Penicillium spp. and Aspergillus spp., while to the high incidence of Fusarium spp. in not controlled conditions storage, reduced vigor of lot 1. The incidence of Xanthomonas spp. was high in all evaluated periods, with difference between lots, however this did not reflect in reduction of physiological quality of seeds.